Mamluk Jerusalem An Architectural Study - Burgoyne, Michael Hamilton (Council for British Research in the Levant, 1987)
A survey of Mamluk architecture in the Old City of Jerusalem carried out by the British School of Archaeology in Jerusalem (BSAJ), beginning in 1968. It is authored by Michael. Hamilton Burgoyne, with additional historical research by D.S. Richards and published on behalf of the BSAJ by the World of Islam Festival Trust.